Pendampingan Pembuatan Laporan Keuangan Menggunakan Aplikasi Akuntansi Sederhana Ms. Excel pada Persaudaraan Salimah PC Bojong Gede Kabupaten Bogor - Hasanudin, Hasanudin; Widiyanti, Wiwik; Susilowati, Isnurrini Hidayat; Marginingsih, Ratnawaty (Jurnal Abdimas Ekonomi dan Bisnis, 2023)
The Salimah Sisterhood is an organization whose members are mostly MSME owners in Bojong Gede District, Bogor Regency. The obstacle encountered by partners is a lack of knowledge and skills in making financial reports, so that profit and loss calculations are only based on rough calculations. The aim of this community service is to provide training in making simple financial reports using an accounting application in the form of Microsoft Excel, which is easy to use. The community service method is carried out in the form of training, starting with group discussion forums, partner situation analysis, pretests, main training activities, and posttests. The results of this community service activity show that there has been an increase in the knowledge, skills, and abilities of partners in preparing their financial reports.